Childhood Trauma and the Severity of past Suicide Attempts in Outpatients with Cocaine Use Disorders. Issue 1 (December 2022) - Icick, Romain; Karsinti, Emily; Brousse, Georges; Chrétienneau, Clara; Trabut, Jean-Baptiste; Belforte, Beatriz; Coeuru, Philippe; Moisan, Delphine; Deschenau, Alice; Cottencin, Olivier; Gay, Aurélia; Lack, Philippe; et al.
Introduction: Suicide attempts have been associated with both cocaine use disorder (CocUD) and childhood trauma. We investigated how childhood trauma is an independent risk factor for serious and recurrent suicide attempts in CocUD. Method : 298 outpatients (23% women) with CocUD underwent standardized assessments of substance dependence (Diagnostic and Statistical Manual—mental disorders, fourth edition, text revised), impulsiveness, resilience, and childhood trauma, using validated tools. Suicide attempts history was categorized as single vs. recurrent or non-serious vs. serious depending on the lifetime number of suicide attempts and the potential or actual lethality of the worst attempt reported, respectively. Bivariate and multinomial regression analyses were used to characterize which childhood trauma patterns were associated with the suicide attempts groups. Results : 58% of CocUD patients reported childhood trauma. Recurrent and serious suicide attempts clustered together and were thus combined into "severe SA." Severe suicide attempt risk increased proportionally to the number of childhood traumas (test for trend, p  = 9 × 10 −7 ). Non-severe suicide attempt risk increased with impulsiveness and decreased with resilience. In multinomial regression models, a higher number of traumas and emotional abuse were independently and only associated with severe vs. non-severe suicide attempts (effect size = 0.82, AUC = 0.7). The study was limited by its cross-sectional design. Conclusion : These preferential associations between childhood trauma and severe suicide attempts warrant specific monitoring of suicide attempts risk in CocUD, regardless of the severity of addiction profiles.